Development of The Last Glacier Mobile Game - Loh, Wei Wen; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2021)
Global warming is a worldwide issue observed since the development of the pre-industrial period. This issue affected climate change and increase the temperature of the planet, which continue to affect a series of global issues such as the increment of sea level and decrement of the glacier. However, these issues can be controlled and reduced by cooperating with people who start to be eco-friendly. For example, take public transport rather than private transport and carry out 3R (recycling, reuse, and reducing). Hence, The Last Glacier mobile game promotes this knowledge to the youngster from seven years old and above using the gamification approach. Game Development Life Cycle (GDLC) is used to develop The Last Glacier Mobile Game. This application developed with Unity and Blender furthermore followed the guidance of GDLC, including releasing the application for Android based. Moreover, the application is tested by alpha testing and beta testing. It has gained positive feedbacks from the target users. 40% of responders very satisfied with the game, 56.67% of responders satisfied with the functionality, and 56.67% of responders satisfied with the performance of the proposed application. However, several enhancements of the mobile game for future works are suggested such as apply unlock features to the levels, enhance the smoothness of the joystick, provide more shop items and update more game levels to make the application more advanced in performance.